Negotiating pathways for the continuation of chhaupadi system in remote parts of Nepal - Bam, Aina Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
Chhaupadi system, the practice of menstrual segregation of women in separate sheds called chhaugoths, is rooted deeply in Mid-western and Far-western parts of Nepal since long ago. In spite of its evil status identified in society menstrual segregation has been witnessed continuing in traditional society. This study has been carried out in order to investigate negotiating pathways for the continuation of the evil practice, focusing the study to one of the representative traditionalist society called Patala in Kalikot district of Nepal. The respondents were comprised of 150 sample sizes consisting of menstruating women from various age group, religious persons, faith healers, activists, and aged people. The data collected showed the low literacy rate in this study site and all the families observed have made menstrual huts (chhaupadi goths). The main reason for the continuation of this evil practice of chhaupadi is it becomes a tradition for this area and the second most reason is the widespread illiteracy as found in this area shown by the data collected. God will get angry if they try to get rid of this practice, some of the respondents answered. Untouchability, restrictions, taboos, segregation resulting in humiliation, health risks, crimes and injustice have often been observed as violation in physical and mental health of women. The people of this area are fed up with this evil tradition. They are trying to get rid of this system but they cannot.